Water penetration through cracks in self-healing cementitious materials with superabsorbent polymers studied by neutron radiography. (November 2018) - Snoeck, D.; Van den Heede, P.; Van Mullem, T.; De Belie, N.
Abstract: SuperAbsorbent Polymers (SAPs) are a promising admixture to obtain self-sealing and self-healing cementitious materials. They are able to physically block water penetration through cracks due to their swelling ability. This is very useful in a cementitious material which is prone to cracking leading to a reduced durability. The effectiveness of counteracting water penetration is of concern. Neutron radiography was performed in order to investigate the influence of SAPs on the water permeability through healed cracks with respect to a reference material without SAPs. The gravimetrically measured capillary absorption corresponded with the obtained results after image analysis and a quantitative analysis could be made. SAPs enhance the water impermeability and are able to seal and heal a crack effectively up to 100 μm. The healing was a main factor to impede water movement through cracks. This will lead to less water ingress in building infrastructures and a possible longer service life.